Sobre o Teorema da Função Inversa - Tezoto, Leandro [UNESP] (2014)
The aim of this work is to present the Inverse Function Theorem as well some applications on the existence of solution for equations. The demonstration of the Inverse Function Theorem is given by a identify perturbation theorem, which is a consequence of the Banach point fix Theorem. In order to prove such results, we present some basics elements of metric spaces and calculus in Banach spaces